Early sorafenib‐related adverse events predict therapy response of TACE plus sorafenib: A multicenter clinical study of 606 HCC patients. Issue 4 (8th June 2016) - Zhao, Yan; Li, Hailiang; Bai, Wei; Liu, Jueshi; Lv, Weifu; Sahu, Sonia; Guan, Sheng; Qin, Xiao; Wang, Wenhui; Ren, Weixin; Mu, Wei; Guo, Weidong; et al.
Abstract : The purpose of our study was to test the hypothesis that sorafenib‐related dermatologic adverse events (AEs) as an early biomarker can predict the long‐term outcomes following the combination therapy of transarterial chemoembolization (TACE) plus sorafenib (TACE‐S). The intermediate‐stage hepatocellular carcinoma patients who received either TACE‐S or TACE‐alone treatment were consecutively included into analysis. In the TACE‐S group, patients with ≥ grade 2 dermatologic AEs within the first month of sorafenib initiation were defined as responders; whereas those with < grade 2 were defined as nonresponders. In the TACE‐S group, the median overall survival (OS) of the responders was significantly longer than that of nonresponders (28.9 months vs. 16.8 months, respectively; p = 0.004). Multivariate analysis demonstrated that nonresponders were significantly associated with an increased risk of death compared with responders (HR = 1.9; 95% confidence Interval‐CI: 1.3–2.7; p = 0.001). The survival analysis showed that the median OS was 27.9 months (95% CI: 25.0–30.8) among responders treated with TACE‐S vs.18.3 months (95% CI: 14.5–22.1) among those who received TACE‐alone ( p = 0.046). The median time to progression was 13.1 months (95% CI: 4.4–21.8) in the TACE‐S group, a duration that was significantly longer than that in the TACE‐alone group [5 months (95% CI: 6.4–13.3), p = 0.014]. This study demonstrated that sorafenib‐related dermatologic AEs are clinical biomarkers to identify responders from all of the patients for TACE‐S therapy. Sorafenib‐related dermatologic AEs, clinical biomarkers, can predict the efficacy of TACE‐S in future randomized controlled trials. Abstract : What's new? For patients with unresectable hepatocellular carcinoma (HCC), combined therapy using transarterial chemoembolization plus sorafenib (TACE‐S) can potentially offer significant survival benefits. However, clinical biomarkers to determine whether TACE‐S is appropriate for unresectable HCC are lacking. This study shows that sorafenib‐related dermatologic adverse events, which appeared within the first month of the start of TACE‐S, serve as a signal of response to TACE‐S for intermediate‐stage HCC patients. TACE‐S therapy, not in all, but in responders to sorafenib, results in longer overall survival compared with TACE alone therapy.